Analysis of strawberry ripening by dynamic speckle measurements - Mulone, C. (2013)
This work seeks to determine the age of a fruit from observation of its dynamic speckle pattern. A mobile speckle pattern originates on the fruit's surface due to the interference of the wavefronts reflected from moving scatterers. For this work we analyzed two series of photographs of a strawberry speckle pattern, at different stages of ripening, acquired with a CMOS camera. The first day, we took ten photographs at an interval of one second. The same procedure was repeated the next day. From each series of images we extracted several statistical descriptors of pixel-to-pixel gray level variation during the observation time. By comparing these values from the first to the second day we noticed a diminution of the speckle activity. This decay demonstrated that after only one day the ripening process of the strawberry can be detected by dynamic speckle pattern analysis. For this study we employed a simple new algorithm to process the data obtained from the photographs. This algorithm allows defining a global mobility index that indicates the evolution of the fruit's ripening.